Cytotoxicity, Antiproliferative and Apoptotic Effect of n-Hexane Fraction of Lime Parasite (Dendrophtoe pentandra) - Subandrate Subandrate; Masayu Farah Diba; Salni Salni; Triwani Triwani; Sri Nita (Universitas Jenderal Soedirman, 2019)
Breast cancer is one of the biggest causes of death in women in the world. Lime parasite (Dendrophtoe pentandra (L.) Miq.), a folk remedy used by Indonesian people, is believed to be efficacious as anticancer drug. This research aims to know the activity of n-hexane fractions of lime parasite in inhibiting the proliferation and apoptosis of T47D cells in vitro. Cytotoxic test with MTT method assay from n-hexane fractions used a multilevel concentration. Antiproliferative test was carried out by the method of MTT assay and cell doubling time was calculated at the time of duplication. Apoptotic test was done with concentration of 1 IC50and ½ IC50which was analyzed by flow cytometry. The results reveals that fractions of lime parasite have cytotoxic activity with concentration of IC50is included in moderatecytotoxic level. The result of the doubling time of the optimum fraction of n-hexane is in 31 hours with the concentration of ¼IC50. Results for the flow cytometry shows the fraction of n-hexane does not induce apoptosis in cells of T47D. Those results show that the active fraction of lime parasite has cytotoxic activity which is able to inhibit proliferation, but does not induce apoptosis of T47D cell.